Домашняя юридическая энциклопедия: Женщинам - Айвазова С. Г. (АСТ : Олимп, 1999)
Экземпляры: ЧЗ (20151127) / Инвентарный номер: 36033 / Цена: 28.00 / Сис.шифр: 67.400.7 / Авт.знак: Д 66 / ГРНТИ: 10 / ББК: 67.400.7